An Athletic Coach–Delivered Middle School Gender Violence Prevention Program: A Cluster Randomized Clinical Trial - Miller, Elizabeth (JAMA Pediatr, 2020)
IMPORTANCE: Adolescent relationship abuse (ARA) and sexual violence (SV) reported among adolescents point to the need for prevention among middle school–age youths. OBJECTIVE: To test an athletic coach–delivered relationship abuse and sexual violence prevention program among middle school male athletes. DESIGN, SETTING, AND PARTICIPANTS: An unblinded cluster randomized clinical trial from spring 2015 to fall 2017 at 41 middle schools (38 clusters). The study included 973 male middle school athletes (ages 11-14 years; grades 6-8; participation rate 50%) followed up for 1 year (retention 86%). INTERVENTIONS: Coaching Boys Into Men (CBIM) is a prevention program that trains athletic coaches to talk to male athletes about (1) respectful relationship behaviors, (2) promoting more gender-equitable attitudes, and (3) positive bystander intervention when harmful behaviors among peers are witnessed. MAIN OUTCOMES AND MEASURES: The primary outcome was change in positive bystander behaviors (ie, intervening in peers’ disrespectful or harmful behaviors); secondary outcomes were changes in recognition of what constitutes abusive behavior, intentions to intervene, gender-equitable attitudes, and reduction in recent ARA/SV perpetration (at end of sports season and 1-year follow up). RESULTS: Of the 973 participants, 530 were white (54.5%), 282 were black (29.0%), 14 were Hispanic (1.4%), and the remainder were multiracial, other race/ethnicity, or not reported. Positive bystander behaviors increased at end of sports season and at 1-year follow-up (relative risk, 1.51; 95% CI, 1.06-2.16 and 1.53; 95% CI, 1.10-2.12, respectively) as did recognition of abuse (mean risk difference, 0.14; 95% CI, 0.01-0.27 and 0.14; 95% CI, 0.00-0.28, respectively). At 1-year follow-up, among those who ever dated, athletes on teams receiving CBIM had lower odds of reporting recent ARA/SV perpetration (odds ratio, 0.24; 95% CI, 0.09-0.65). Gender attitudes and intentions to intervene did not differ between study arms. In exploratory intensity-adjusted and per protocol analyses, athletes on teams receiving CBIM were more likely to report positive bystander behaviors and to endorse equitable gender attitudes and less likely to report ARA and sexual harassment perpetration 1 year later. CONCLUSIONS AND RELEVANCE: An athletic coach–delivered program for middle school male athletes is an effective strategy for reducing relationship abuse among younger adolescents. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02331238